Mechanisms of anterior cruciate ligament injury in world cup alpine skiing: a systematic video analysis of 20 cases. Issue 4 (27th March 2011) - Bere, T; Flørenes, T W; Krosshaug, T; Koga, H; Nordsletten, L; Irving, C; Muller, E; Reid, R C; Senner, V; Bahr, R
Abstract : Background: We have limited insight into the mechanisms of anterior cruciate ligament (ACL) injuries in alpine skiing, particularly among professional ski racers. Objective: To describe the mechanisms of ACL injury in World Cup alpine skiing. Design: Descriptive video analysis. Setting: World Cup alpine skiing. Methods: 20 cases of ACL injuries reported through the International Ski Federation Injury Surveillance System for three consecutive World Cup seasons (2006–2009) were obtained on video. Seven international experts performed visual analyses of each case to describe the injury mechanisms in detail (skiing situation, skier behaviour, biomechanical characteristics). Results: Three main categories of injury mechanisms were identified: the slip-catch, landing back-weighted and the dynamic snowplow. The slip-catch mechanism accounted for half of the cases (n=10), and all these injuries occurred during turning, without or before falling. The skier lost pressure on the outer ski, and while extending the outer knee to regain grip, the inside edge of the outer ski abruptly caught in the snow, forcing the knee into internal rotation and valgus. The same loading pattern was observed for the dynamic snowplow (n=3). The landing back-weighted category included cases (n=4) where the skier was out of balance backwards in-flight after a jump and landed on the ski tails with nearly extended knees. The suggested loading mechanism was a combination of tibiofemoral compression, boot induced anterior drawer and quadriceps anterior drawer. Conclusion: A consistent pattern was observed where the main mechanism of ACL injury in World Cup alpine skiing appeared to be a slip-catch situation where the outer ski suddenly catches the inside edge, abruptly forcing the outer knee into internal rotation and valgus. A similar loading pattern was observed for the dynamic snowplow. Injury prevention efforts should focus on the slip-catch mechanism and the dynamic snowplow.